Electronic and optical properties of halide double-perovskites under strain: a density functional study. Issue 20 (18th October 2021) - Zarabinia, Nazila; Rasuli, Reza
ABSTRACT: Halide double perovskite has emerged as a novel class of semiconducting materials to solve the challenges of Pb-based halide perovskite solar cells such as instability, toxicity, and humidity. In this work, we studied the electronic structure of Cs2 AgBiX6 (X = Br, Cl, I) as a halide double perovskite using density functional theory. The band structures, the density of states, and optical properties were calculated under different strain values. The induced strain can estimate the behavior of the halide double perovskite in a realistic condition such as coating layer, stress by another layer, doping with other material, or reducing to a monolayer. Our results show that under 6% tensile strain, the indirect band gap of Cs2 AgBiI6 converts to the direct band gap, which shows contributions from both Ag (d) and Bi (p) orbitals at the band edges. The halide double perovskite, Cs2 AgBiI6, in the normal state indicates an indirect band gap with a value of 0.48 eV due to the hybridizing of Ag (s) and Bi (s) orbitals at the band edges. The band gap increases under tensile strain as well as the optical band gap. The optical band gap is slightly higher than the electronic band gap with a value of 1.4 eV for the normal state where this value becomes 2.3 eV for 6% strained halide double perovskite. Our results show Cs2 AgBiI6 can be valuable for its photo-electronic application.